Role of VEGF-A and Its Receptors in Sporadic and MEN2-Associated Pheochromocytoma - Carla Vaz Ferreira (International Journal of Molecular Sciences, 2014)
Pheochromocytoma (PHEO), a rare catecholamine producing tumor arising from the chromaffin cells, may occurs sporadically (76%–80%) or as part of inherited syndromes (20%–24%). Angiogenesis is a fundamental step in tumor proliferation and vascular endothelial growth factor (VEGF-A) is the most well-characterized angiogenic factor. The role of angiogenic markers in PHEO is not fully understood; investigations were therefore made to evaluate the expression of VEGF-A and its receptors in PHEO and correlate to clinical parameters. Twenty-nine samples of PHEO were evaluated for VEGF-A, VEGF receptor-1 (VEGFR-1) VEGFR-2 expression and microvessel density (MVD) by immunohistochemistry. Clinical data were reviewed in medical records. The mean age of patients was 38 ± 14 years, and 69% were woman. VEGF-A, VEGFR-1 and VEGFR-2 staining were detected in nearly all PHEO samples. No significant correlation was observed between VEGF-A, VEGFR-1, VEGFR-2 expression or MVD and age at diagnosis, tumor size or sporadic and hereditary PHEO. However, the levels of expression of these molecules were significantly higher in malignant PHEO samples (p = 0.027, p = 0.003 and p = 0.026, respectively).VEGF-A and its receptors were shown to be up-regulated in malignant PHEO, suggesting that these molecules might be considered as therapeutic targets for unresectable or metastatic tumors.